Susceptibility of Anopheles gambiae complex mosquitoes to microbial larvicides in diverse ecological settings in western Kenya. Issue 2 (9th January 2019) - Derua, Y. A.; Kahindi, S. C.; Mosha, F. W.; Kweka, E. J.; Atieli, H. E.; Zhou, G.; Lee, M.‐C.; Githeko, A. K.; Yan, G.
Abstract: The microbial larvicides Bacillus thuringiensis var. israelensis ( Bti ) and Bacillus sphaericus ( Bs ) (Bacillales: Bacillaceae) are well known for their efficacy and safety in mosquito control. In order to assess their potential value in future mosquito control strategies in western Kenya, the current study tested the susceptibility of five populations of Anopheles gambiae complex mosquitoes (Diptera: Culicidae), collected from five diverse ecological sites in this area, to Bti and Bs under laboratory conditions. In each population, bioassays were conducted with eight concentrations of larvicide ( Bti / Bs ) in four replicates and were repeated on three separate days. Larval mortality was recorded at 24 h or 48 h after the application of larvicide and subjected to probit analysis. A total of 2400 An. gambiae complex larvae from each population were tested for their susceptibility to Bti and Bs . The mean (± standard error of the mean, SEM) lethal concentration values of Bti required to achieve 50% and 95% larval mortality (LC50 and LC95 ) across the five populations were 0.062  (± 0.005) mg/L and 0.797 (± 0.087) mg/L, respectively. Corresponding mean  (± SEM) values for Bs were 0.058 (± 0.005) mg/L and 0.451 (± 0.053) mg/L, respectively. Statistical analysis indicated that the five populations of An. gambiae complex mosquitoes tested were fully susceptible to Bti and Bs, and there was no significant variation in susceptibility among the tested populations. Abstract : Bacillus thuringiensis var. israelensis ( Bti ) and Bacillus sphaericus ( Bs ) are environmentally safe biolarvicides proven to be effective and recommended for malaria vector control. By utilizing a mode of action that differs from that of synthetic insecticides, these biolarvicides have the potential to delay or control the evolution of insecticide resistance in malaria vectors. Their efficacy, high level of safety for non‐target organisms and potential to control both indoor and outdoor biting vectors make these biolarvicides ideal for use in integrated vector management operations.